EDXRF and FTIR Analysis of Some Glass Fragments Belong to Ottoman Period, Excavated in Ancient Ainos (Enez) Turkey - Akyuz1, Tanil; Akyuz1, Sevim; Basaran2, Sait; Cakan2, Banu (Asian Journal of Chemistry, 2013)
Ancient glass fragments excavated in the archaeological district Enez (Ancient Ainos), Turkey were investigated by combined energy dispersive X-ray fluorescence (EDXRF) and Fourier Transform Infrared (FTIR) spectrometry techniques. Multi-elemental contents of a spirally twisted translucent yellow glass bracelet, fragment of a turquoise blue vessel and its cover and a fragment of a translucent white vase decorated with a surface coating, that belong to Ottoman period were determined by EDXRF method. The concentrations of 23 elements (Na, Mg, Al, Si, S, K, Ca, Ti, Cr, Mn, Fe, Co, Cu, Zn, As, Br, Rb, Sr, Sb, Ba, Ce, U, Pb) which might be present in the samples as flux, stabilizers, colorants or opacifiers and impurities, were examined. The glasses were classified as potassium-limy glass. IR reflection and absorption spectroscopy enable us to determine structural characteristics of the glasses.